Some Problems of Minors Access to Justice - E. F. Rashidov; J. P. Chulkov (Сибирское юридическое обозрение, 2013)
Some peculiarities of minors entry into civil procedure are revealed in the article. The conclusion is made about the necessity of non-adults admissibility at the age of 14-18 to have the right to take a legal action independently in all cases of material legal ability and capacity.